2018
DOI: 10.1038/s41594-018-0035-7
|View full text |Cite
|
Sign up to set email alerts
|

Oocyte DNA damage quality control requires consecutive interplay of CHK2 and CK1 to activate p63

Abstract: The survival rate of cancer patients is steadily increasing, owing to more efficient therapies. Understanding the molecular mechanisms of chemotherapy-induced premature ovarian insufficiency (POI) could identify targets for prevention of POI. Loss of the primordial follicle reserve is the most important cause of POI, with the p53 family member p63 being responsible for DNA-damage-induced apoptosis of resting oocytes. Here, we provide the first detailed mechanistic insight into the activation of p63, a process … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
158
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 127 publications
(178 citation statements)
references
References 52 publications
11
158
0
Order By: Relevance
“…Activation can be suppressed using selective inhibitors of ATM, CHK2 and CK1, suggesting that tetramerization is based on the same pathway as activation following the treatment with cisplatin or doxorubicin (Supplementary Fig. 1a) 13,14,18 . In order to investigate the time dependent induction of apoptosis, we measured the ratio of germ cell nuclear acidic peptidase (GCNA) 19 positive and cleaved poly(ADP-ribose)-polymerase 1 (PARP1) double positive cells in whole mouse ovaries using our 3D staining and light sheet-based fluorescence microscopy combined with semi-automated segmentation method (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation can be suppressed using selective inhibitors of ATM, CHK2 and CK1, suggesting that tetramerization is based on the same pathway as activation following the treatment with cisplatin or doxorubicin (Supplementary Fig. 1a) 13,14,18 . In order to investigate the time dependent induction of apoptosis, we measured the ratio of germ cell nuclear acidic peptidase (GCNA) 19 positive and cleaved poly(ADP-ribose)-polymerase 1 (PARP1) double positive cells in whole mouse ovaries using our 3D staining and light sheet-based fluorescence microscopy combined with semi-automated segmentation method (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first step of the kinase cascade is the activation of checkpoint kinase 2 (CHK2) or checkpoint kinase 1 (CHK1) by ataxia telangiectasia mutant kinase (ATM) 11 . Activated CHK2 phosphorylates TAp63α on S582 12 which renders TAp63α a substrate for casein kinase 1 (CK1) 13 . CK1 requires pre-phosphorylated substrates with the consensus sequence pS/T-x-x-S/T, where pS/T is a phosphorylated serine or threonine.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because controlling the quality of the oocytes that are fertilized, implant, and become fetuses should be a top priority in the evolutionary design of the female reproductive tract, it was suggested that oocytic atresia functions to eliminate genetically defective oocytes (Stearns and Ebert 2001). The mechanisms involved are being discovered: one is DNAdamage-induced apoptosis of resting oocytes mediated by p63, a member of the p53 family (Tuppi et al 2018). Oocyte death can also be triggered by defects in the synapsis and recombination of chromosomes during meiosis that produce double strand breaks, which also induce apoptosis (Qiao et al 2018).…”
Section: The Quality Control Hypothesismentioning
confidence: 99%
“…Another study demonstrated that CHK2 inhibitor II hydrate affected the activities of a broad spectrum of kinases and impacted the global repression of the DNA damage response (DDR) in cultured ovaries 10 , thereby raising some questions about its specificity. Tuppi et al reported that CHK2 and the executioner kinase CK1 are both involved in the TAp63a-mediated oocyte degeneration in cultured ovaries exposed to chemotherapy 11 . As cultured mouse ovaries exposed to chemotherapeutic drugs may not recapitulate the signaling pathways physiologically occurring in the ovary in vivo, we aimed to perform all our experiments under in vivo conditions.…”
Section: Introductionmentioning
confidence: 99%